MIKROKONTROLER SISTEM HYBRID UNTUK PENGATURAN SUHU DAN KELEMBABAN INKUBATOR BAYI - Pranata, Andrian Indra; Widhiada, W.; Adnyana, W. Bandem (Teknik Desain Mekanika, 2022)
Abstract The rapid growth of technology in Indonesia, especially in the health sector, is very interesting to follow. Even so, the infant mortality rate in Indonesia is still a problem that haunts this country. One of the factors contributing to the high infant mortality rate in Indonesia is the death of babies born prematurely. Babies born prematurely require special care, especially in maintaining the ambient temperature in the range of 35?C-36?C. By using the Incubator this can be achieved. The baby incubator is a means of preventing hypothermia (a condition of difficulty regulating body temperature which leads to difficulty coping with cold pressure) in newborns, especially premature babies by warming the room temperature and the baby in order to maintain a normal baby's body temperature (Harseno, 2017). In this study, modeling of an incubator with an Arduino Mega 2560 microcontroller and 2 Arduino Uno microcontrollers is carried out which is integrated with each other and the researcher will implement a PID control system and Fuzzy Logic which is arranged in a Hybrid manner with the help of Matlab and Arduino.ide software. Using temperature parameters with a set point of 36oC and humidity with a RH range of 60-80%. With the target temperature signal error on the system ? 5% and the maximum system overshoot temperature ? 5%. The results of this study obtained an average signal error = 0.0462% and maximum overshoot = 0.83378% in the no-load test. The average signal error = 0.018202% and maximum overshoot = 1.36083% in the test with a load of 2 Kg. Keyword : Babies Born Prematurely, Incubator, Temperature Control, PID, Fuzzy Logic, Hybrid